Analisis Faktor Penerimaan Dan Penggunaan Aplikasi Palui Baiman Menggunakan Technology Acceptance Model (TAM) - Husnul Khatimi; Muhammad Alkaff; Muhammad Ridho A.G.D. (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2022)
The application of E-Government is a solution about how efforts to increase and benefit are obtained by the community from public services designed by the government under Mayor Regulation Number 41 of 2018 concerning E-Government Implementation utilizing Information Technology by forming an Android-based information system with the name Application Integrated Kelurahan Administration Services or can be called the "Palui Baiman" application. The Palui Baiman application is an application that can facilitate the means of submitting letters at the village level. The problem that arises is how the Palui Baiman application can be accepted by the people of Banjarmasin City. The objectives achieved in this study were to determine the level of acceptance and use of the people of Banjarmasin City towards the Palui Baiman application by applying the Technology Acceptance Model (TAM) and using the usefulness and convenience variables integrated with the acceptance variable. Based on the results of the analysis by applying multiple linear regression testing, it was concluded that the Palui Baiman application was able to increase public acceptance and use with the Banjarmasin City Government raising the value of ease of use of the application with the results obtained of 0.016.